2022
DOI: 10.1002/iid3.609
|View full text |Cite
|
Sign up to set email alerts
|

Blood myxovirus resistance protein‐1 measurement in the diagnostic work‐up of suspected COVID‐19 infection in the emergency department

Abstract: Introduction: Myxovirus resistance protein 1 (MxA) is a biomarker that is elevated in patients with viral infections. The goal of this study was to evaluate the diagnostic value of MxA in diagnosing COVID-19 infections in the emergency department (ED) patients. Methods: This was a single-center prospective observational cohort study including patients with a suspected COVID-19 infection. The primary outcome of this study was a confirmed COVID-19 infection by RT-PCR test. MxA was assessed using an enzyme immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A recent study shows that MxA could be used as a part of COVID-19 diagnostics in patients with suspected COVID-19 infection. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study shows that MxA could be used as a part of COVID-19 diagnostics in patients with suspected COVID-19 infection. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…A recent study shows that MxA could be used as a part of COVID-19 diagnostics in patients with suspected COVID-19 infection. [10] Severe COVID-19 is associated with dysregulation of the interferon response [11]. Rapid recognition of viral RNA by Toll-like receptors 3 and 7 and RIG-I-like receptors induces a type I IFN response that may suppress viral replication, whereas activation of the cGAS-STING pathway by macrophages as a result from endothelial cell damage induces a prolonged elevation of type I IFNs which may induce aberrant inflammation and is associated with poor clinical outcome [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is mechanistically conceivable that immunosuppressive therapy impairs the type I interferon immune response, previous studies demonstrated that MxA is a reliable marker for viral infections in immunocompromised children after allogenic stem cell transplantation or chemotherapy [ 23 , 24 ]. A recent report showed that MxA is also valuable for identifying SARS-CoV2-infected patients, regardless of their immune status [ 25 ]. In accordance with these results, we observed no difference in monocyte MxA expression in immunocompromised compared to immunocompetent adults with viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients, MxA measurements in whole blood could differentiate patients with viral infections from non-infections and bacterial infections in the ED [ 9 , 10 ]. In ED patients suspected of COVID-19 infection, higher MxA levels were reported in patients with COVID-19 compared to those with other infections [ 10 , 11 ]. The integration of CRP for identifying bacterial infections and MxA for identifying viral infections into a unified diagnostic test holds the potential to reliably distinguish between bacterial and viral infections.…”
Section: Introductionmentioning
confidence: 99%